EGR cylinder deactivation strategy to accelerate the warm-up and restart processes in a Diesel engine operating at cold conditions. (April 2022) - Galindo, José; Dolz, Vicente; Monsalve-Serrano, Javier; Bernal Maldonado, Miguel Angel; Odillard, Laurent
The aftertreatment systems used in internal combustion engines need high temperatures for reaching its maximum efficiency. By this reason, during the engine cold start period or engine restart operation, excessive pollutant emissions levels are emitted to the atmosphere. This paper evaluates the impact of using a new cylinder deactivation strategy on a Euro 6 turbocharged diesel engine running under cold conditions (−7°C) with the aim of improving the engine warm-up process. This strategy is evaluated in two parts. First, an experimental study is performed at 20°C to analyze the effect of the cylinder deactivation strategy at steady-state and during an engine cold start at 1500 rpm and constant load. In particular, the pumping losses, pollutant emissions levels and engine thermal efficiency are analyzed. In the second part, the engine behavior is analyzed at steady-state and transient conditions under very low ambient temperatures (−7°C). In these conditions, the results show an increase of the exhaust temperatures of around 100°C, which allows to reduce the diesel oxidation catalyst light-off by 250 s besides of reducing the engine warm-up process in approximately 120 s. This allows to reduce the CO and HC emissions by 70% and 50%, respectively, at the end of the test.